Investigating the factors affecting adherence to inhaled corticosteroids in patients with asthma using primary care data in the UK - Taylor, Amelia C. (2017)
Background: Poor adherence to inhaled corticosteroids (ICS) is known as the main cause for therapeutic failure in asthma treatment and associated morbidity. Adherence is complex and can have many causes, which will vary between conditions, treatments and patients. To improve adherence, it is vital to understand what effects a patients adherence, so appropriate interventions can be developed and targeted, both for the patients who would benefit most and at the most important points in treatment. Very few studies have characterised the variables associated with poor adherence and how these differences may change over time, and the most appropriate methodology for investigating this relations have not previously been defined. Aims and objectives: The aim of the PhD study was to investigate what characteristics associated with a patient’s adherence to ICS, and to investigate whether these relationships change over time using a large primary care dataset. The objectives included the development of a longitudinal measure of asthma patients’ adherence to ICS, then to investigate the time dependent relationship between adherence and other available patient variables by trialling a number of different methods. In addition, the effect of adherence on clinical outcome in asthma was tested, since counter intuitively many studies have not previously found a clear relationship between the variables. Methods: A retrospective longitudinal study using a large cohort was conducted using primary care data from the Clinical Practice Research Datalink (with Hospital Episodes Statistics data) between 1997 and 2010. Asthma patients aged between 12 and 65 years, without a diagnosis of chronic obstructive pulmonary disease were included in the study cohort. ICS prescriptions were extracted and used to calculate the annual prescription possession ratio (PPR). Several definitions of the PPR measure were tested to develop a proxy measure to represent adherence. Variables related to clinical outcomes and other characteristics were also identified for each patient in the cohort. A two-way analysis was conducted to compare the relationship between adherence and each patient variable with time, and then four methods were used to further investigate the relationship between adherence and patient exacerbations including; (1) comparing adherence in the year before and after an exacerbation; (2) descriptively exploring the clinical outcomes associated with different adherence levels; (3) identifying the relative risk of an exacerbation associated with adherence defined by different cut off levels of PPR; and (4) descriptively exploring the effect of adherence on outcome and outcome on adherence over time. Finally, the available variables associated with adherence (including previous adherence and clinical outcomes) were analysed in a dynamic panel model to understand explore the effect of variables on patients’ adherence to ICS which allows for the feedback effects of previous adherence and clinical outcome and the effect of time on adherence. Results: Many patient variables were found to effect adherence. When modelling the effect of patient variables on adherence, adherence was found to be lower in younger patients (+0.11%/year), patients with fewer years in the study (+0.25%/year), with more severe asthma (step 5 patients had a 3.32% lower PPR than step 2 patients), with good control (5.21% lower), with lower previous adherence (-0.51% per % PPR), and who had not previously experienced an exacerbation (0.87% lower compared with patients who had experienced no primary car exacerbation and 1.45% lower for those who experienced no secondary care exacerbation). Adherence increased with patient year, consistently across most subgroups, with the following exceptions; the 20-25 year old age group had lower initial adherence (53.9%) than the younger patients (58.3%), patients registered in the East Midlands had the lowest adherence (57.7%), but increased over time to become the highest (90.7%) and in the first year of the study the adherence for patients treated at step 2 of the guidelines was the lowest (57.5%) but it increased over time to become the second highest step (85.7%). Conclusion: This longitudinal follow-up study using electronic patient records over time was useful to identify the effect of multiple patient variables on adherence. The main characteristics associated with poor adherence were the characteristics that we would associate with better health, or less severe asthma. Therefore, the interventions to improve adherence or to review the appropriateness of treatment should be developed to target younger patients, early on in treatment before they have experienced an exacerbation of their asthma symptoms. The PPR measure developed was useful to measure changes in adherence over time, as a measure of the maximum amount of medicine that the patient had available to them, expressed as a percentage of their recorded prescribed dose. However there are some important limitations to the PPR measure including most importantly that adherence must be measured against a routinely prescribed daily dose of ICS and medicine prescribing and not medicine taking is measured, meaning that adherence is likely to be overestimated. The methods used to analyse the adherence measure had not previously been used to assess adherence in asthma. By using the results from each analysis method, information about different parts of the relationship between adherence and other patient variables including their exacerbation risk and time could be combined, which uniquely allowed the longitudinal measurement and analysis of adherence in asthma over extended study duration.